PENGARUH KEPEMIMPINAN, KEPUASAN KERJA, MOTIVASI KERJA DAN KOMITMEN ORGANSASI TERHADAP KINERJA MANAJER MADYA DI RUMAH SAKIT PEMERINTAH - RUMENGAN, GRACE S. (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to find out the effects of leadership, job satisfaction, work motivation and organization commitment on the middle manager performance of public hospitals. The research was conducted at the public hospitals in Jakarta and Padang, West Sumatera. The sample size was 75 middle managers at M. Djamil, Fatmawati and Persahabatan hospitals by random sampling technique. The data were analyzed by descriptive, regression and path analysis methods. The results showed the followings: 1) there is a significant direct effect of the leadership on the job satisfaction and work motivation and 2) there was also a significant direct effect of job satisfaction and work motivation on the organization commitment and manager performance. 3) there is a significant indirect effect of leadership, the organization commitment and manager performance on the job satisfaction and work motivation. To get improvement of the middle managers performance of public hospitals, the research result may be used as the consideration.Keyword: leadership, job satisfaction, work motivation, organization, performance